Schemes of high-voltage pulse shapers on the basis of stepped transmition lines for high-current accelerators - Gordeev, V.S. (Вопросы атомной науки и техники, 1999)
The systems of high-voltage pulses formation in the majority of high-current accelerators with pulse duration from several to hundreds ns are designed on the basis of single or double pulse forming lines. The disadvantage of these systems consists for a number of applications in the relatively low output voltage equal in the matched mode for a double forming line to the charging voltage while for a single line – only to a half of this value.